Architecting the Telecommunication Evolution: Toward Converged Network Services - Gurbani, Vijay (CRC Press, 2009)
Service-oriented architecture (SOA) uses services as the baseline for developing new architectures and applications, as networks are built specifically to satisfy service requirements. Most services are currently handled over different networks, but newer services will soon require cross-network support. Architecting the Telecommunication Evolution: Toward Converged Network Services outlines the challenges of providing crossover services and the new architectures and protocols that will enable convergence between circuit- and packet-switched networks.